Landscape Ecological Structures and Patterns for Green Space Conservation in Forest Monasteries in Northeast Thailand: 10.32526/ennrj/22/20240016 - Kongsombut, Prat; Pattanakiat, Sura; Rawang, Wee; Srijuntrapun, Pattranit; Phewphan, Uthaiwan; Phutthai, Thamarat; Vongvassana, Sirasit; Jumpasingha, Jirapatch (Environment and Natural Resources Journal, 2024)
The green spaces in Wat Pah play an important role in forest conservation in Thailand. This study identified and analyzed the structures and patterns of landscape ecology in Wat Pah Nanachart, Ubon Ratchathani Province, to guide a conceptual framework for green space conservation in forest monasteries. Spatial analysis and modeling using geoinformatics technology were employed to recognize and characterize these landscapes. Information on the green space conservation and management of Wat Pah was also obtained using an in-depth interview and site observation. The results revealed that most of the green space in Wat Pah is forest, characterized by an ecological matrix and a dry evergreen forest. The forest structure can be divided into three canopies, dominated by the Dipterocarpaceae family, which has regenerated into upper and lower canopies. It is an edge matrix and ecological corridor connected to the internal and external green spaces of Wat Pah. It plays an important role in supporting cultural, religious, and aesthetic activities for ordained monks and Buddhists. The spatial landscape model can be divided into three main zones: Thoranisangha, Buddhawas, Sanghawas. Thoranisangha is an open space covered with traditional and artificially planted tree species. It is located in front of the temple and designed for public utilities in the context of managing and conserving the remaining trees. Buddhawas is a semi-open space mostly covered with traditional tree species. It represents Buddhism’s identity and uniqueness and is used for religious ceremonies and dissemination—listening to sermons, meditating, and praying. Meanwhile, Sanghawas is covered with natural forest and contains residences for monks that are designed to be in harmony with the forest ecosystem.